Pengaruh Pembelajaran Berbasis Proyek dalam Keterampilan Berbicara Siswa Kelas X DPB SMK Negeri 1 Soppeng - Hasnawati, Hasnawati; Sultan, Sultan; Saleh, Muhammad (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe the learning outcomes of 10th-grade DPB students at SMK Negeri 1 Soppeng before and after implementing the project-based learning model (PjBL), and to determine its effect on students' speaking skills. This study used a quantitative approach with a one-group pretest-posttest pre-experimental design. The sample consisted of 21 students selected from a population of 41 students. Data collection was conducted through presentation tests, which were then analyzed using descriptive and inferential statistics. The results showed that the average pre-test score was 43 (low category), while the average post-test score increased to 78 (high category). The t-test showed a significance value of 0.000 <0.05, indicating a significant effect of project-based learning on students' speaking skills. These findings indicate that the Project-Based Learning (PjBL) model is effective when implemented in vocational learning contexts to actively and meaningfully improve students' speaking skills.